Block combination–based asynchronous wake-up schedule in wireless sensor networks - Woosik Lee; Teukseob Song (International Journal of Distributed Sensor Networks)
In wireless sensor networks, when sensor nodes are operated with different ratios of active slots, this is called asymmetric duty cycles. Furthermore, cycles with the same ratio of active slots per cycle for all nodes are called symmetric duty cycles. In wireless sensor networks, most applications require both symmetric and asymmetric duty cycles. The balanced incomplete block design–based wake-up schedule is known to be the optimal solution for symmetric duty cycles. However, because this schedule cannot support asymmetric duty cycles, the balanced incomplete block design–based wake-up schedule is not suitable for wireless sensor networks. Herein, we propose a new scheme called the block combination–based asynchronous wake-up schedule to resolve this issue for asymmetric duty cycles. Block combination–based asynchronous wake-up schedule combines different blocks using a block combination operation. The combined schedule guarantees common active slots between sensor nodes in asymmetric duty cycles. To demonstrate the superior performance of block combination–based asynchronous wake-up schedule, we implement a TOSSIM-based simulation and compare the experimental results with recent neighbor discovery protocols such as balanced incomplete block design, prime-based block design, Disco, U-Connect, SearchLight, Hedis, and Todis. We then prove that block combination–based asynchronous wake-up schedule outperforms the others.